An examination of the reliability and validity of the recovery capital questionnaire (RCQ). (1st March 2022) - Burns, John; Yates, Rowdy
Abstract: Aims and Background: Recovery capital refers to the resources people can call upon to initiate and sustain alcohol and drug problem resolution. Measuring this phenomenon could help an individual better understand their strengths as well as gauge the impact of any interventions designed to improve recovery capital and / or reduce addiction severity. This study aimed to test the internal consistency, stability reliability, criterion-related concurrent validity and content validity of the Recovery Capital Questionnaire (RCQ). Setting and participants: Participants (n = 173) accessing community based addiction treatment (n = 108) and residential treatment (n = 65) in England and Scotland completed the RCQ at two time-points one week apart (n = 102) to test stability reliability, and also completed the RCQ alongside measures of quality of life and resilience (n = 152). Content validity was assessed by seven subject matter experts with content validity ratio and index calculated. Findings: Cronbach's Alpha values (internal consistency) included: social α = 0.52 (0.40–62); physical α = 0.73 (0.66–0.78); human α = 0.85 (0.82–0.88); community α = 0.85 (0.82–0.88); RCQ Total α = 0.88 (0.85–90). RCQ stability reliability (r = 0.89) and ICC (0.88) were calculated. Content Validity Index statistic of 0.91 was calculated. Correlations between relevant domains within the RCQ and WHOQOL Bref were found to include: r = 0.44, 0.59, 0.66 and 0.40. Correlations between RCQ and CD-RISC scores were calculated (r = 0.65). Conclusion: The Recovery Capital Questionnaire was found to possess good overall internal consistency and stability reliability. Content validity was found to be strong and the RCQ demonstrated good concurrent validity with a measure of quality of life and a measure of resilience. Highlights: Recovery Capital Questionnaire results correlate with Quality of Life measure. Recovery Capital Questionnaire results correlate with resilience measure. Recovery Capital Questionnaire possesses strong content validity. Recovery Capital Questionnaire demonstrate acceptable internal reliability. Recovery Capital Questionnaire demonstrates good-to-excellent stability reliability.